Factors Affecting Pregnancy Complications in Ghana - Yaw K. Wiafe; Andrews Asamoah; Patricia Akweongo; Augustine Kumah (Global Journal on Quality and Safety in Healthcare)
Introduction The prevalence of maternal mortality continues to be a significant health concern across the world. In Ghana, pregnancy-related complications in the previous 5 years account for 12% of all deaths among women 15 to 49 years. More than half of these deaths were avoidable if early assessment had been done. However, assessment of the pooled prevalence of pregnancy-related complications among pregnant women to inform policy is limited. This study sought to determine the factors contributing to pregnancy complications in Ghana. Methods Using a systematic sampling technique, a facility-based cross-sectional study was conducted among 415 pregnant women who attended antenatal care (ANC) services at Mamprobi Hospital. Bivariate and multiple logistics regression analyses were conducted to test significant factors determining pregnancy complications. The results of regression analysis are reported in odds ratio. Statistical significance was set at p < 0.05. Results The mean age of the participants was 31.6 ± 6.6 years. The incidence of pregnancy complications among the pregnant women was 51.8% (95% CI, 0.47–0.56) The incidence of pregnancy complications among the women was significantly determined by age (adjusted odds ratio [AOR], 6.1; CI, 1.19–30.76), record of pregnancy complication (AOR, 2.5; CI, 1.35–4.49), ANC visit (AOR, 6.1; CI, 2.14–17.70), and family history of pregnancy complication (AOR, 3.6; CI, 1.25–10.40). Other significant factors included a record of abortion (AOR, 7.8; CI, 4.21–14.32), knowledge about obstetric danger signs (AOR, 2.4; CI, 1.21–4.88), and experiencing at least one obstetric danger sign during pregnancy (AOR, 6.6; CI, 3.30–13.29). Conclusion The incidence of pregnancy complications was comparatively high among the women who used ANC services at Mamprobi Hospital. Early initiation of ANC services for pregnant women is an essential tool for addressing some of the challenges of early onset of some pregnancy complications, including anemia in pregnancy and preeclampsia. Midwives and other health workers who engage pregnant women should encourage their clients to initiate ANC visits at an early stage.